Lateralities and asymmetries of the orthostatic posture - Helbert, Serge (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Man’s body has a large number of asymmetries, some are in relation with regulation of the tonic postural activity, we generally name them asymmetries of the orthostatic posture and others are in relation with phenomena of cortical lateralization, we sometimes name them gestural asymmetries. The correlation between these two types of asymmetries is a controversial subject. And actually this study presents facts that are incoherent: either the correlation is very strong or very low between these two types of corporal asymmetries. A possible signification of these inconsistencies is discussed which seems to highlight the role of the vision.